Politics and Green Financial Crime: Envisioning a Sustainable Democratic Future in Indonesia - Yagie Sagita Putra; Pujiyono Pujiyono; Nur Rochaeti; Zico Junius Fernando (Faculty of Law Universitas Jenderal Soedirman, 2024)
The Indonesian Financial Transaction Reports and Analysis Center (PPATK) in Indonesia has uncovered a significant issue concerning illegal financial transactions linked to environmental crimes. They have identified that approximately 1 trillion Rupiah, obtained from such green financial crimes, is being funnelled into political parties for the 2024 elections. This discovery is particularly alarming, as it raises serious concerns about the integrity of the democratic process and the sustainability of the nation's political future. The PPATK's findings indicate that this illegal funding comes from various environmental crimes, including illegal logging and other environmentally damaging activities. The fact that these funds are being used to finance political campaigns implies a deeply concerning intersection between environmental crime and political corruption. This situation exemplifies a broader category of 'green financial crime', where environmental exploitation is directly linked to illicit financial gains. Results This research investigates the implications of these financial irregularities for the country's commitment to environmental conservation and the development of green policies. It discusses the broader implications for Indonesia's democratic order and urges a re-evaluation of current political funding mechanisms, advocating for transparent and accountable practices to ensure electoral integrity and promote a sustainable democratic future. The importance of collective action, involving civil society, policymakers, and international partners, to address the linkages between politics, democracy, and green financial crime ultimately protects Indonesia's democratic values and environmental heritage.